Recombinant TrxAFNIIx4His6 improves post‑thaw motility of ram sperm measured by a sperm motility tracker software - Ledesma, Alba Verónica (2021)
The aim of the present study was to evaluate a freezing extender supplemented with recombinant TrxAFNIIx4His6, a reported decapacitating factor. Semen samples were diluted in tris-egg yolk medium with 0, 1.5 µM and 3.0 µM of TrxAFNIIx4His6. Computer-assisted sperm motility tracking and subpopulations evaluation showed that addition of TrxAFNIIx4His6 improved post-thaw total and progressive motility at both concentrations evaluated. TrxAFNIIx4His6 increased the sperm subpopulation with the highest progressiveness and great velocity and decreased the subpopulation of poorly motile and almost non-progressive sperm. Incorporation of TrxAFNIIx4His6 to freezing extender shows potential for the development of cryoprotection media which may lead to improved fertility after artificial insemination.